Avoiding electromechanical instability or loss of tension of dielectric elastomer generators with position-controlled cycles for enhanced energy harvesting. (1st September 2022) - Fan, Peng; Zhu, Zicai; Lu, Tongqing
Abstract: The maximum energy density of a dielectric elastomer generator (DEG) represents the potential energy harvesting capacity, which is determined by the material failure modes. The maximum energy density and the failure modes of DEGs in a force-controlled energy harvesting cycle have been evaluated. However, the position-controlled energy harvesting cycle that is widely used in DEGs has not been investigated. This paper explores the energy harvesting capacity of DEGs with rigid and flexible connections in a position-controlled cycle. The failure modes in a position-controlled cycle are analyzed and the electromechanical instability of DEGs with rigid and flexible connections is mainly focused on. On this basis, we study the maximum energy density of DEGs with diverse connections under different loading configurations. The results show that, compared with the force-controlled cycle, the position-controlled cycle can enhance the energy harvesting capacity of DEGs due to the avoidance of electromechanical instability or loss of tension. The conclusions and methods can help to evaluate the energy harvesting capacity and provide a safe region for the optimal design of DEGs in a position-controlled cycle.